PELATIHAN PEMBUKUAN KEUANGAN SEDERHANA UNTUK UMKM TOKO BUNDA DESA PABEAN DRINGU PROBOLINGGO - Oktaviani, Dewi Anggun; Lidyana, Novita; Priantono, Seger; Hartanti, Aprilia; Zuhroh, Mimik Umi; Baihaqi, Mas Ahmad; Halimah, Nur (Abdi Panca Marga, 2023)
Jalan Yos Sudarso, Pabean Village, Dringu District, Probolinggo Regency, East Java Province, is a village where the majority of the population are MSMEs and run the Toko Bunda business. The main problem faced by Toko Bunda business owners in Pabean Village is the limited knowledge and insight they have in business management regarding the preparation of financial reports. Therefore, the aim of this service is to help improve the ability of MSMEs to carry out bookkeeping that is simple and easy to understand. The method used in carrying out community service in South Alai Village is an approach method of socializing how to make simple financial report bookkeeping to grocery stores around the village. The results of the activities carried out are that business actors state that implementing bookkeeping in businesses has a positive effect and is very important for businesses to use in order to know how to calculate business profits or losses and measure business capabilities. Keywords: MSME, Simple Bookkeeping, Financial Records